Epidemiological profile of symptomatic osteoarthritis in older adults: a population based study in Dicomano, Italy. Issue 6 (1st June 2003) - Mannoni, A; Briganti, M P; Di Bari, M; Ferrucci, L; Costanzo, S; Serni, U; Masotti, G; Marchionni, N
Abstract : Objectives: To assess the prevalence of hand, hip, and knee osteoarthritis (OA) in an older Italian community dwelling population and its association with disability. Method: A cross sectional survey of the whole community aged 65 years and over, was carried out in Dicomano, a small rural town in Tuscany, Italy. Subjects were screened by geriatricians for major chronic conditions, including hip, knee, and hand OA, using diagnostic algorithms based on the American College of Rheumatology (ACR) clinical criteria. A rheumatologist examined subjects who screened positive. Disability was assessed by a World Health Organisation questionnaire. Results: 697 of 864 eligible subjects (81% of the eligible population) were screened. OA of the knee, hand, or hip was identified by clinical ACR criteria respectively in 159, 139, and 81 subjects, and was confirmed by the rheumatologist in 158/182 (87%), 75/101 (74%), and 63.2% of cases. The estimated prevalence was 29.8%, 14.9%, and 7.7%, respectively. Only hip OA was significantly associated with disability in basic activities of daily living. Conclusions: About one third of community dwelling older people are affected by symptomatic peripheral OA. Hip OA was strongly associated with disability.